If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(-4u+8)-5u=5(u+7)-9
We move all terms to the left:
-6(-4u+8)-5u-(5(u+7)-9)=0
We add all the numbers together, and all the variables
-5u-6(-4u+8)-(5(u+7)-9)=0
We multiply parentheses
-5u+24u-(5(u+7)-9)-48=0
We calculate terms in parentheses: -(5(u+7)-9), so:We add all the numbers together, and all the variables
5(u+7)-9
We multiply parentheses
5u+35-9
We add all the numbers together, and all the variables
5u+26
Back to the equation:
-(5u+26)
19u-(5u+26)-48=0
We get rid of parentheses
19u-5u-26-48=0
We add all the numbers together, and all the variables
14u-74=0
We move all terms containing u to the left, all other terms to the right
14u=74
u=74/14
u=5+2/7
| 21-7d=1-2d | | 6+z/3=1 | | 2x+22=5(x+2) | | -24z-15=-27 | | 5y+14=7y | | 3(w+3)-7w=-15 | | 9x+3-(x-1)=6(x+10) | | 18-6.3z=49.5 | | 9x+3-x-1=6(x+10) | | x+x.05=252 | | 10g-2(8+5g)=16 | | 9m+1m=3m+13 | | 20.1/5+d=23 | | 5x-6=(x-1 | | x²-6x+9=-9x+19 | | x−5=−122.−4x=28 | | 8x²-56x=0 | | 4/9x+20=-5(4x+2)-30 | | 56x=8² | | 271/2-5x=31/2 | | 5x=7x-96 | | 2b−1=5 | | 6x-6=8x+10 | | 54=-620x | | 2(2.4x+4)=4.1x+7+3.1x | | 2w-14.5=27.3 | | -25+4n=75 | | (14+-2i)(7+12i)=122+154i | | (1/4)*x+17=x-4 | | n+7+n+2n-12+3n+4=90-n | | 15x+15=12x-12 | | 2x=12-5x |